Concept Of Wound Healing Described In Sushruta Samhita- Boon For Modern Scientific Era - Sharma, Nisha; srivastav, Sanjay; gupta, Rajesh (International Research Journal of Ayurveda & Yoga, 2021)
Sushruta samhita is the pillar of Ayurveda. Acharya Sushruta described almost every common and critical clinical problem and its management. From starting of civilization vrana is one of the common diseases which have been managed by human being. Acharya described surgical, Para surgical and medicinal treatment of wounds. A wound is a major health problem because of high risk of complications which causes not only physical & mental trauma but financial burden also to the patient. So, the diagnosis and treatment both are important for wound management. Phases of wound are very important point to study for the accurate and speedy wound healing. So, in this document, efforts have been made to describe the wounds healing according to Sushruta samhita because the concept of wound management described the Acharya Sushruta has proved as boon for modern scientific era.